Local buckling of RHS members under biaxial bending and axial force - Vieira, Luís (2018)
The authors of this paper gratefully acknowledge the financial support provided by the Research Fund for Coal and Steel project RFCS-2015-709892, “Overall Slenderness Based Direct Design for Strength and Stability of Innovative Hollow Sections – HOLLOSSTAB”.